PERBANDINGAN LEMBAGA ANTI KORUPSI DI INDONESIA, SINGAPURA DAN HONGKONG - rahmiati; Trias Saputra; Nurhafni; Muhammad Sobih (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2021)
The act or crime of corruption is contrary to the social and economic values of the citizens, so corruption should be classified as an abnormal or anusual crime. For this reason, the action against corruption itself should be done in an unusual way, which then becomes a differentiator from various other crimes. One type of action in dealing with corruption is to establish a special institution that aims to determine how corruption can be eradicated. In this country, such an institution is called the corruption eracation commission (KPK). The KPK institution was born in early 2002 based on law No 30/2002 on the KPK. In fact, the KPK itself is not the first institution in Indonesia to specifically address corruption. Before the KPK was created, in Indonesia there had also been bodies that had the same task and function. The KPK can be said to be a “new kid” whwn compared to special anti-corruption institutions in other Asian countries, such as Singapore (CPIB/ Corrupt Practices Investigation Investigation Bureau) and Hong Kong (ICAC/ Independent Commission Against Corruption). CPIB from Singapore and ICAC from Hong Kong one of the “role model” anti-corruption institusions in Asia that have many achievements in the field of eracating corruption in their countries. The methodology in this research Is made using a juridical model that is normative in nature, which in the process uses in the realm of harmonious juridical law, appropriate books or literature.